Weathering a Storm : Survey-Based Perspectives on Employment in China in the Aftermath of the Global Financial Crisis - Giles, John; Park, Albert; Cai, Fang; Du, Yang (2012)
Evidence from a range of different sources suggests that Chinese workers lost 20-36 million jobs because of the global financial crisis. Most of these layoffs affected migrant workers, who have typically lacked employment protection, tend to be concentrated in export-oriented sectors, and were among the easiest to dismiss when the crisis hit. Although it was severe, the employment shock was short-lived. By mid-2009, the macroeconomic stimulus and other interventions had succeeded in boosting demand for migrant labor. By early 2010, abundant evidence pointed to scarcity in China's labor market, as labor demand was once again leading to brisk growth in wages.The paper reviews different available sources of evidence for the effects of the crisis, and notes the biases associated with alternative ex post efforts to measure the employment effects of the crisis. In particular, the paper highlights the usefulness of household surveys with employment histories relative to surveys based on sampling through firms.